Joule heating and viscous dissipation effects in hydromagnetized boundary layer flow with variable temperature - Naseem, Tahir; Fatima, Urooj; Munir, Mohammad; Shahzad, Azeem; Kausar, Nasreen; Nisar, Kottakkaran Sooppy; Saleel, C. Ahamed; Abbas, Mohamed (ELSEVIER, 2022)
By taking variable temperature, we consider an MHD boundary layer flow past a flat plate with radiation, joule heating, and viscous dissipation effects. The suitable similarity transformation is used to obtain ODEs from governing non-linear coupled PDEs, which are solved by the engaging shooting method. The mechanical energy is converted to thermal energy due to addition of dissipation; the temperature variations in the fluid and their characteristics are investigated. On a two-dimensional flow, the impacts of the temperature power coefficient (n), Prandtl (Pr) and Eckert numbers (Ec), and the magnetic parameter (M), are graphically presented. The rate of heat transfer is calculated for different parameters and presented in the form of tables. It is found that as the Eckert number grows, the temperature profile increases, and as the Prandtl number increases, the temperature profile reduces.
Keywords: MHD Boundary layer; Viscous dissipation; Joule heating; Radiation effect; Rosseland number; Similarity transformation; FLAT-PLATE; NATURAL-CONVECTION; MIXED CONVECTION; STRETCHING SHEET; LAMINAR-FLOW; SLIP-FLOW; FLUID; RADIATION; Thermodynamics